Cloud Collaboration: Its Effect toward Writing Achievement and Impact toward Attitude to Learning - Dedi Kurniawan; Lingga Agustina Suganda; Zuraida Zuraida (Universitas Jambi, Indonesia, 2020)
The study aims at finding out the effect of cloud collaboration toward writing achievement and students’ perception toward its impact to attitude of English learning. It was an experimental study with pretest-posttest control group design, and the forty-eight samples of which were randomly taken from seventy-nine students taking paragraph writing course. The data were collected using an adapted writing test and cloud service impact questionnaire. The data from the test were analysed using t-test, while the data form questionnaire were descriptively analysed. The results show that there was an increase of writing achievement before and after the treatment and the increase was caused by the cloud collaboration implementation. The results also report that the cloud collaboration implementation had a high positive impact toward students’ confidence, affective engagement and behavioural engagement to English learning, especially in writing course.